Positive design and appreciative construction from sustainable development to sustainable value - Thatchenkery, Tojo Joseph; Cooperrider, David L.; Avital, Michel (Advances in appreciative inquiry ;, 2010)
This volume is focused on sustainable value which has become a widespread aspiration in all walks of life. By taking a generative approach and by building on positive design principles inherent in the appreciative inquiry methodology, we propose moving from sustainable development to sustainable value. what several articles, including David's on Sustainable innovationut design in scrimination that you feel so stChapters focus on three thematic areas. Contributors to the first one, positive design for sustainable value, respond to questions such as: How can the design approach help enhance the sustainable value over profit value? What needs to happen to create a vibrant community of practice among design practitioners, scientists, business and political leaders? Contributors to the second thematic area, Appreciative Intelligence and Social Innovation for Sustainable Value, provide case studies that will show that by reframing global problems with an appreciative lens, organizations of all sorts can indeed create social innovation and even establish a business case for sustainable value. The third thematic area is focused on social entrepreneurship for sustainable value. Social entrepreneurship bridges the gap among established organizations such as the businesses, and citizen initiatives and has the greatest potential for validating sustainable value as a legitimate goal for organizations of all sorts. Organizations such as the Ashoka have demonstrated the power of wide-spread social entrepreneurship. Contributors to this area provide lessons learned from high impact social entrepreneurship and conceptualize how this nascent movement with unbridled potential may contribute to the radical shift necessary for moving from sustainable development to sustainable value.